Expert one-on-one J2EE development without EJB - Johnson, Rod, 1970- (Wrox expert one-on-one., 2004)
The book begins by examining the limits of EJB technology - what it does well and not so well. Then the authors guide you through alternatives to EJB that you can use to create higher quality applications faster and at lower cost - both agile methods as well as new classes of tools that have evolved over the past few years.